2022
DOI: 10.1016/j.jctube.2021.100293
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring prolongation of QT interval in patients with multidrug-resistant tuberculosis and non-tuberculous mycobacterium using mobile health device AliveCor

Abstract: Multidrug resistant tuberculosis and non-tuberculous mycobacterium infections present challenges due to complex treatment regimens. Extended treatment regimes expose patients to higher risks of toxic side-effects. A high drug toxicity profile necessitates closer monitoring. One of the more challenging issues is QTc prolongation with non-injectable regimens. This study investigates the portable AliveCor device to record and measure the QTc on a 6-lead ECG. An automated QTc readout from 12-Lead ECG fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The device proved useful for ECG monitoring in these patients, detecting ECG abnormalities significant enough to promote a change in treatment in 17.4% of them. Puranik et al ( 23 ) investigated the AliveCor device to monitor the QT interval in patients with multidrug-resistant tuberculosis and non-tuberculous mycobacterium. For 13 patients, a comparison was made between an automated QTc readout from the 12-lead ECG, and the mean QTc value was calculated from each patient's respective AliveCor device tracing (lead II).…”
Section: Resultsmentioning
confidence: 99%
“…The device proved useful for ECG monitoring in these patients, detecting ECG abnormalities significant enough to promote a change in treatment in 17.4% of them. Puranik et al ( 23 ) investigated the AliveCor device to monitor the QT interval in patients with multidrug-resistant tuberculosis and non-tuberculous mycobacterium. For 13 patients, a comparison was made between an automated QTc readout from the 12-lead ECG, and the mean QTc value was calculated from each patient's respective AliveCor device tracing (lead II).…”
Section: Resultsmentioning
confidence: 99%
“…15 Chapter 4 Systematic review results t he literature searches of bibliographic databases conducted for this EVA systematic review, including additional scoping searches conducted to identify costs and cost-effectiveness studies, identified 8505 unique references. After initial screening of titles and abstracts, 28 references were considered to be potentially relevant and ordered for full paper screening; of these 10 publications, 26,31,34,37,[39][40][41][42][43] relating to six studies, were included in the review. A further three publications, one provided by NICE/ Specialist Committee Members (SCMs) 14 and two provided by the manufacturer of KardiaMobile 6L, AliveCor, 51,52 were assessed and included in the review.…”
Section: Methods Of Analysis/synthesismentioning
confidence: 99%
“…Based on the searches and inclusion screening described above, 13 publications, 14,26,31,34,37,[39][40][41][42][43]51,52 relating to 8 studies, and 2 additional unpublished reports, 53,54 were included in this review; the results section of this report cites studies using the primary publication only.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations